Conference Report: Transforming drug discovery and development through innovation: past, present and future. (February 2013) - Needham, Shane; Premkumar, Noel; Pols, Joanna; Lee, Mike
This annual meeting began in 1998 and was the first industry-led event to focus on the specific needs of industry researchers. The goal of Clinical and Pharmaceutical Solutions Through Analysis (CPSA) is to provide an in-depth review of innovative technology and industry practices through open discussion of industry-related issues and needs. Education and specialized training are the foundation of all CPSA events. As the industry has evolved so has CPSA. Thus, the year the name was changed from Chemical and Pharmaceutical Structural Analysis to CPSA was to reflect the growing focus on clinical applications and the emergence of personalized medicine. Most importantly, the CPSA annual meeting has retained the same high-quality scientific content, open interaction from industry opinion leaders and a collegial environment.